The genotoxic evaluation and gane expression studies of cadmium uptake in hybrid tilapia (oreochromis sp.) - Govindasamy, Vijayendran
Toxic heavy metals especially cadmium are growing threat to global environmental health. To respond to these problems, there has been large demand for the new ways for assessment o f environment pollution, which are fast, reliable and accurate.